The impact of COVID-19 on hypertensive patients and multiprofessional performance: an integrative review (Research, Society and Development, 2023)
Objective: to describe the factors that impact the progression and severity of coronavirus infection in hypertensive patients, as well as identify coping actions that control this morbidity. Methodology: An integrative review of publications available in the MEDLINE, LILACS and SciELO databases was carried out from June to July 2021. The search terms used were: “Hypertension” AND “COVID-19” AND “Chronic Disease”. Results: Eight articles were identified and included for the review. The factors addressed were categorized into three groups of common issues: Immunological factors; Antihypertensive therapy and Social and public health factors. The main impacts include lymphocytopenias, severe pneumonias and lethal growth. Conclusion: Hypertensive patients are negatively impacted by the COVID-19 pandemic, with important reactions and increased mortality. However, the literature still presents disagreements about the real factors that contribute to a worse clinical outcome.